Antiviral response and resistance analysis of treatment‐naïve HCV‐infected patients receiving single and multiple doses of GS‐9190. Issue 8 (23rd March 2016) - Mo, H.; Hedskog, C.; Svarovskaia, E.; Sun, S.‐C.; Jacobson, I. M.; Brainard, D. M.; McHutchison, J. G.; Miller, M. D.
Summary: GS‐9190 is a NS5B non‐nucleoside analogue with demonstrated effectiveness in a Phase 1 monotherapy study and in combination with other DAAs for treatment of chronic HCV infection. Here, the resistance profile of GS‐9190 monotherapy in a Phase 1b study was investigated. Resistance analysis was performed by population sequencing and allele‐specific PCR (AS‐PCR) for Y448H with an assay cut‐off of 0.5%. Phenotypic susceptibility analyses were performed on patient isolates as well as site‐directed mutagenesis of mutations selected during monotherapy. No resistance‐associated variants were observed in patients before or after receiving single doses of GS‐9190 by population sequencing. In contrast, in patients who received GS‐9190 for 8 days, mutations Y448H and Y452H in NS5B were observed by population sequencing in 21/36 (58%) and 2/36 (5.6%) patients, respectively, at Day 8 or Day 14. Among the remaining 15 patients who had no detectable Y448H at Day 8 or Day 14 by population sequencing, low frequencies of Y448H ranging from 1.3 to 9.7% were detected in 14 of 15 patients by AS‐PCR. By AS‐PCR, Y448H remained detectable at reduced frequency in the majority of patients analysed through 4–6 months of follow‐up. Chimeric HCV replicons constructed with the NS5B sequence from patients with Y448H and Y448H + Y452H/Y demonstrated 27‐fold and 78.5‐fold reduced susceptibility to GS‐9190. In conclusion, Y448H was rapidly selected in the majority of patients receiving multiple doses of GS‐9190 as monotherapy, despite undetectable levels in pretreatment samples. Y448H confers reduced susceptibility to GS‐9190 and other NNIs and persisted in most patients for months post‐treatment.